1998
DOI: 10.1046/j.1460-9568.1998.00057.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐affinity copper block of GABAA receptor‐mediated currents in acutely isolated cerebellar Purkinje cells of the rat

Abstract: The actions of Cu2+ ions on GABAA receptor-mediated currents in acutely isolated Purkinje cells from rat cerebellum were studied using the whole-cell patch-clamp technique and a rapid perfusion system. Bath application of Cu2+ reduced currents induced by 2 microM gamma-aminobutyric acid (GABA) in a concentration-dependent manner with an IC50 of 35 nM. The Cu2+-induced block of GABA responses was not voltage-dependent. Increasing the GABA concentration (from 2 to 50 microM) decreased the blocking effect of Cu2+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 23 publications
(29 reference statements)
2
46
1
Order By: Relevance
“…Effects of exogenous copper have been reported for several types of ion channels (73)(74)(75), but the binding sites are unknown. Recently, Li et al (76) reported effects of reducing agents on the Torpedo ClC-0 chloride channel, but exogenous copper (10 M) was without effect.…”
Section: Discussionmentioning
confidence: 99%
“…Effects of exogenous copper have been reported for several types of ion channels (73)(74)(75), but the binding sites are unknown. Recently, Li et al (76) reported effects of reducing agents on the Torpedo ClC-0 chloride channel, but exogenous copper (10 M) was without effect.…”
Section: Discussionmentioning
confidence: 99%
“…2 To whom correspondence should be addressed. (20). To exclude that the observed histamine effects depend on the complexation of such divalent cation contaminations, potentiation and dose-response curves experiments were performed in Ringer's solution prepared with ultrapure water (AMPUWA water, Fresenius, Bad Homburg, Germany) as suggested (20).…”
Section: Methodsmentioning
confidence: 99%
“…Cu 2ϩ inhibition of olfactory bulb neurons was similar to that of dorsal root ganglion neurons (Trombley and Shepherd, 1996). However, in cerebellar Purkinje cell GABA A receptor currents, maximal Cu 2ϩ block was only 60% and the IC 50 was lower (35 nM) (Sharonova et al, 1998) than in dorsal root ganglion neurons. Variations in Cu 2ϩ pharmacology may come from different region-specific GABA A receptor subunit subtype combinations.…”
Section: Discussionmentioning
confidence: 85%
“…However, several recent studies have shown that Cu 2ϩ inhibited GABA A receptor currents in native and transfected cells (Ma and Narahashi, 1993;Narahashi et al, 1994;Fisher and Mac-This study was supported by National Institutes of Health grant NS33300 (to R.L.M.). donald, 1998;Sharonova et al, 1998). In addition, Cu 2ϩ inhibited ␣-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid, N-methyl-D-aspartate, and glycine receptor currents (Trombley and Shepherd, 1996;Vlachova et al, 1996;Weiser and Wienrich, 1996) and blocked long-term potentiation in hippocampus (Doreulee et al, 1997).…”
mentioning
confidence: 99%